Effect of the Inspiring leadership to Achieve Organizational health in the Iraq Organization Field research in the Iraqi Ministry of Culture - محمد علي عالية جواد (Journal of Economics and Administrative Sciences, 2019)
The aim of the research is to know the characteristics of both variables in order to be able the to construct the integrated framework of its paragraphs through the available information on both inspirational leadership and organizational health. as fundamental variables of research, as well as the extent of the influence of the inspirational variable as an independent variable in the organizational health variable as a variable in its three physical, mental and social dimensions. The research is important to stimulate the behavior side of the staff. Which is one of the top concerns of senior management in the ministry, because of its great importance in increasing the effectiveness of the performance of employees and their loyalty to their ministries, which is achieved through the direct impact of the leader in persuasion and guidance and give positive motivation is the best example for them. Touched Seathaly basic problem in ministry (sample for research) discussed the existence of a leadership believes in the achievement of well-being and happiness of employees during work reflected on the job satisfaction of employees and their performance on their association with their organization and their work. Has sought research to achieve a number of cognitive and practical goals to a set of key and subsidiary assumptions and through the adoption of a questionnaire to collect data and information related to research in the Iraqi ministry of culture in Baghdad as a sample for research, which consisted of( 32) people from the administrators of various levels depending on personal interviews and field visits to collect data related to the research where the subject of data collection for statistical analysis using a program(spss) program (statistical package for social science). and relying on a number of statistical methods to address these data and to reach a set of results including the arithmetic mean and the standard deviation of the correlation coefficient and the coefficient of influence which showed the relationship of correlation and positive effect between the variable leadership inspirational and the dimension of organizational health and the search reached a set of results، including the need to work promote the dimensions of regulatory health variable to achieve better performance for the staff of the organization، to increase their loyalty to their organization and inspirational leadership has a role in changing the behavior of employees to improve the level performance، training, welfare and happiness, the search also presented a number of suggestions including the importance of training staff, studying all obstacles and addressing them to achieve the organizational health, implementing the incentive system and the spreading the teams knowledge among them ..